2008
DOI: 10.1016/j.jnoncrysol.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rogue particles on the sub-surface damage of fused silica during grinding/polishing

Abstract: The distribution and characteristics of surface cracks (i.e., sub-surface damage or scratching) on fused silica formed during grinding/polishing resulting from the addition of rogue particles in the base slurry has been investigated. Fused silica samples (10 cm diameter x 1 cm thick) were: 1) ground by loose abrasive grinding (alumina particles 9-30 µm) on a glass lap with the addition of larger alumina particles at various concentrations with mean sizes ranging from 15-30 µm, or 2) polished (using 0.5 µm ceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(49 citation statements)
references
References 20 publications
2
47
0
Order By: Relevance
“…Distribution of abrasive contact forces. This result agrees with experiments by Suratwala et al [28]. They showed that in a lapping experiment where a very small fraction (0.1%) of rogue particles were added to a slurry with abrasive grains that were half the size, this increased SSD depth to the same level as in experiments with a slurry containing only the same rogue particles.…”
Section: Discussion About Grinding Wheel Designsupporting
confidence: 91%
“…Distribution of abrasive contact forces. This result agrees with experiments by Suratwala et al [28]. They showed that in a lapping experiment where a very small fraction (0.1%) of rogue particles were added to a slurry with abrasive grains that were half the size, this increased SSD depth to the same level as in experiments with a slurry containing only the same rogue particles.…”
Section: Discussion About Grinding Wheel Designsupporting
confidence: 91%
“…It is interesting as a catalyst in automobile exhaust systems, as a photocatalytic agent, an electrical conductor, an absorber of UV radiation, an additive to other high-tech ceramics, a ceramic electrolyte for intermediate temperature solid oxide fuel cells (ITSOFCs) (500-700°C), etc. [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest and demand for silica nanoparticles not only in scientific field [1,2], but also in industry fields, such as catalysis [3], stabilizers [4], pigments [5] and chemical mechanical polishing [6]. The size and uniformity of the silica particles have great influence on the quality of these products.…”
Section: Introductionmentioning
confidence: 99%